Measuring Orthodontic Treatment Satisfaction: Questionnaire Development and Preliminary Validation - M. Elizabeth Bennett, PhD; J. F. Camiila Tulfoch, BDS, FDS, DOrth (Blackwell Synergy, 2001)
The aims of this study were to develop a reliable self-report measure of consumer satisfaction with orthodontic treatment, and to preliminarily assess its validity.